Irish political writings after 1725 A modest proposal and other works - Swift, Jonathan 1667-1745 (Cambridge University Press, 2018)
This latest volume of The Cambridge Edition of the Works of Jonathan Swift is the first fully annotated edition of Swift's Irish prose writings from 1726 to 1737. Works in this volume include the famous A Modest Proposal, the acerbic A Short View of the State of Ireland, Swift's contributions to The Intelligencer, and other prose pieces of satire, polemic and intervention into contemporary Irish politics. Most of these works have never previously been published with full scholarly annotation, or with a complete and textually authoritative apparatus. This volume offers a comprehensive introduction, setting Swift's writings of the period into their full historical, political and economic context. In addition to a critical introduction and appendices, there is also an up-to-date bibliography. The volume enables Swift's role as a political and social commentator in the years after the publication of Gulliver's Travels to be understood with new clarity